Treatment of Bamboo (Bambusa tulda) with Clay (Kaolinite) and Chemicals: Evaluation of Dimensional Stability and Termite Resistance - Sonowal, Juthika; K. Gogoi, Pradip (Asian Journal of Chemistry, 2010)
Three year old common bamboo (Bambusa tulda) samples were treated with kaolinite clay suspension followed by kerosene oil. Another sample was treated with kaolinite clay suspension and other chemicals (boric acid, copper acetate and Na-salt of diethyldithiocarbamate in sequence) and dimensional stability and termite resistance of the samples were evaluated. It was observed that compared to untreated and simple kaolinite treated sample, the chemical treated samples showed better dimensional stability in terms of antishrink efficiency, increased bulk coefficient, weight percent gain as well as better termite resistance capacity.